How to balance the industrial customers' resources requirements while maintaining energy efficiency? - Jingyi Zhu; Yang Zhang (Journal of Innovation & Knowledge (JIK), 2023)
One of the most important challenges facing the optimal management of power resources for industrial customers is considering the latest available technologies for this purpose. In this regard, this article investigates the most important technologies and methods available in this field and tries to maintain the energy efficiency at a suitable level by presenting a knowledge-oriented approach. One of the most important technologies used in this field is demand response, which provides an opportunity for consumers to provide an appropriate response to energy at various price rates by reducing or changing electricity consumption in peak load. In addition, the emergence of different renewable energy sources such as solar and wind in recent years has created a suitable opportunity for the participation of the majority of industrial and household consumers and as a result has increased social awareness in this field. The above items are investigated and discussed one by one in this paper and the impact of each of them on meeting the needs of industrial customers is assessed. In the end, it is tried to present a model to show how to optimally use these resources in scheduling from the social, economic and technical point of view.
Keywords: A14; C93; C02; Q48; 650; Demand response management; Energy efficiency; Industrial customers; Renewable sources; Social impacts